Determination of urinary 5-hydroxyindoleacetic acid by combining Dμ-SPE using carbon coated TiO2 nanotubes and LC–MS/MS. (November 2015) - García-Valverde, María Teresa; Lucena, Rafael; Cárdenas, Soledad; Valcárcel, Miguel
Background: In this article, carbon coated titanium dioxide nanotubes (TiO2 -NT@C) are employed for the determination of 5-hydroxyindole-3-acetic acid in urine by LC–MS/MS.Results: All the variables involved in the extraction have been studied and optimized in depth. The method has been analytically characterized on the basis of its linearity, accuracy, sensitivity and precision. The LOD is 155.8 μg/l while the repeatability and the reproducibility, expressed as RSD, are better than 5.42 and 5.25%, respectively. The obtained relative recovery is 115%.Conclusion: TiO2 -NT@C permit the efficient extraction of 5-hydroxyindole-3-acetic acid from complex biological samples such as urine allowing its sensitive determination by LC–MS/MS.